Mednarodni center za reševanje investicijskih sporov (ICSID) in Republika Slovenija - Svetličič, Andrej (Podjetje in delo, 2014)
Slovenia is a part of the globalized economy and certain foreign investors have decided to invest in it while Slovenian investors invest in other countries. Investments in another country bring new opportunities as well as risks, the latter being mitigated inter alia by international legal safeguards. A part of those safeguards is a possibility of arbitration between investors and host countries under the ICSID rules. Slovenia has been thus far involved in three such cases as a host country. One of the fundamental conditions for ICSID arbitration jurisdiction is the consent of both parties to the dispute, which can be brought about in different manners, among which bilateral investment treaties (BITs) are the most frequent basis for a state consent. In this respect, due regard should be given to the validity of the BIT and the application of the so-called survival clauses, upon which the validity of the offer of consent by the host country depends. This aspect is one of the key issues with respect to ICSID jurisdiction in the Grassetto case. Based on the experience thus far in the latter case, certain challenges for the internal procedural management of such cases have emerged, such as the competence of line agencies for the administration of the case, legal bases for the appointment of the arbitrator and cost aspects of such arbitrations. Irrespective of the currently relatively rare exposure of Slovenia to such arbitrations, they can imply high costs for the procedure itself and potentially if the investors prevail with their claims, so it would be useful to consider improving the highlighted aspects of internal procedures.
Keywords: arbitražna sodišča; mednarodna arbitraža; pravno varstvo; reševanje; spori; tuje investicije